CONSUMER DECISION MODEL – ENGEL KOLLAT AND BLACKWEL: WEARABLE TECHNOLOGY -SMARTWATCH CONSUMER BEHAVIOR POST COVID-19 PANDEMIC IN SURABAYA - Pitoyo, Didik Joko; Susanti, Christina Esti; Ardhanari, Margaretha (LPPM ITB AAS INDONESIA (d.h STIE AAS Surakarta), 2024)
This research uses quantitative methods using an exploratory factor analysis approach. This research explores the factors that influence consumers' decisions in choosing a smartwatch as a wearable technology that helps monitor health. This research was conducted in Surabaya, East Java and involved 120 respondents to describe data regarding the reasons for choosing a smartwatch as wearable technology that helps monitor health. From the results of the analysis, it was found that seven factors shape the choice of the smartwatch as a health monitoring tool, including social factors, motivational factors, reference factors, cultural factors, service factors, individual factors, and psychological factors.